Teaching narrative theory - Herman, David; McHale, Brian; Phelan, James (Modern Language Association of America options for teaching, 2010)
The last two decades have seen a burst of renewed interest in narrative theory across many academic disciplines as scholars analyze the power of storytelling in print and other media. Teaching Narrative Theory provides a comprehensive resource for instructors who aim to help students identify and understand the distinctive features of narrativity in a text or discourse and make use of the terms and concepts of the field. This volume in the Options for Teaching series is organized to assist teachers at different levels of instruction and in different disciplinary settings. In twenty-one essays, the contributors discuss narrative theory's various teaching contexts (e.g., classes on literature, creative writing, and folklore and ethnography); key concepts and terms (e.g., story and plot, time and space, voice, perspective); applications beyond printed texts (e.g., film and digital media); and impact on other areas of theory (e.g., gender and ethnic studies). A glossary provides a guide to the challenging technical terminology characteristic of the field, and the volume as a whole emphasizes the importance of understanding and implementing technical terms in learning narrative theory.
Keywords: Narration (Rhetoric) : Study and teaching; filmer; opetus; kerronta; narratologia; kirjallisuudentutkimus; narratiivinen tutkimus; media; retoriikka; luova kirjoittaminen; kirjallisuus; undervisning; berättande; narratologi; litteraturvetenskap; narrativ forskning; retorik; kreativt skrivande; litteratur